The Design and Testing of Novel IEC 60601-1-8 Audible Alarms. (September 2016) - Edworthy, Judy; Reid, Scott; McDougall, Siné; Edworthy, Jonathan; Hall, Stephanie
IEC 60601-1-8 is a medical alarms standard concerned with equipment safety. Part of its content specifies a set of audible alarms for eight clinical functions: cardiovascular, drug administration, oxygen, artificial perfusion, power down, temperature, ventilation and a general sound, along with a medium- and a low-priority alarm. It has long been acknowledged that the alarms specified are difficult to learn and retain, (Atyeo and Sanderson 2015; Edworthy, Page, et al, 2014; Lacherez, Seah & Sanderson, 2007; Sanderson, Wee & Lacherez 2006; Wee and Sanderson 2008). The alarm sounds require updating. The project reported here is concerned with developing candidate sets of alarms aimed at replacing those currently specified in IEC 60601-1-8. Four prototype sets of alarms were designed for the eight functions specified in the standard. These were as follows: Word rhythms : Each alarm contains a large number of harmonics and the eight alarms vary in pitch pattern, number of pulses and rhythm where those patterns mimic the words of the functions (so for example the 'Cardiovascular' alarm possesses 6 pulses and contains stresses on the first and fourth pulses). Auditory icons : These are real-world sounds that are used as metaphors for the functions. So for example the cardiovascular alarm is a heartbeat-like sound, the "Oxygenation" sound is an aerosol sound and so on. Auditory icons with beacon : Same as the Auditory icons but possesses a short beacon at the start of the sound in order to signify that it is an alarm sound. Resilient : These sounds are simple metaphors (such as a rising pitch for temperature) created at a sampling rate of 8kHz, intended for use in equipment with poor acoustic reproduction. A fifth set, IEC, is the set currently specified in the standard and was also tested for comparison. Participants were tested on a single set of alarms. Once they had been told the meanings of the eight alarms, they were presented with each of them ten times in a block-randomised fashion, and were required to name the alarm. Analysis of variance on the correct/incorrect scores considered the effect of sound type (IEC, word rhythm, auditory icons, auditory icons plus beacon, resilient), block (blocks 1 to 10) and sound (the individual alarm sounds) on the number of correct responses. Each of these factors showed significant effects, as well as some interactions. The largest effect by a considerable margin was attributable to sound type. Performance was significantly lower for the IEC condition than any of the other conditions; performance for the word rhythm condition was significantly higher than for the IEC condition but significantly lower than the other three conditions; performance in the resilient condition was significantly higher than for both the IEC and the word rhythm conditions but significantly lower than in the auditory icons conditions; and performance in the auditory icons and the auditory icons plus beacon conditions was significantly higher than in all other conditions, and similar to one another.